A study of appendiceal crypt cell adenocarcinoma (so-called goblet cell carcinoid and its related adenocarcinoma). - Nonaka, Daisuke; Papaxoinis, Georgios; Lamarca, Angela; Fulford, Paul E.; Valle, Juan W.; Chakrabarty, Bipasha (Human Pathology, 2017)
Goblet cell carcinoids (GCCs) of the appendix are rare tumors, characterized by a carcinoid-like organoid growth pattern. Despite the term carcinoid, neuroendocrine features are inconspicuous, and its behavior is distinct from carcinoid. Its high grade counterpart is designated as adenocarcinoma ex GCC. We conducted a retrospective study of 105 tumors to find prognostic values of a variety of clinico-pathologic features. The tumors were subclassified as low grade, equivalent to classic type, and high grade, defined as loss of organoid pattern, and a proportion (%) of low and high grades were documented in each tumor. Correlations between survival and various clinico-pathologic parameters were investigated. One-third were pure low grade while the remainder contained variable high grade component ranging 5-95%. Neuroendocrine cell component ranged 0-90% (median 5) while mucus cell component ranged 5-100% (median 70). By univariate analysis, size, stage, high grade component, nuclear grade, surgery and chemotherapy correlated with cancer-related survival (CSS), and by multivariate analysis, stage (P=.001), high grade component (P=.008) and tumor size (P=.005) correlated with CSS. There was significant difference in CSS when the cases were grouped in high grade component